Losing sight of Peru: Replica to Orin Starn - Poole, Deborah (1992)
During the 1980s American anthropology underwent two major transformations. The first involved a turn into history. The second, a turn towards texts. While the first of these led scholars a long way towards understanding the specificity, functioning and concrete reality of the economic, political, discursive and social processes studied by anthropology; the second traveled an exquisite path of self-reflection and disciplinary criticism. When the two paths crossed they produced a salutary historical re-examination of the discursive and institutional origins of anthropology in nineteenth-century colonial and evolutionary thought.